(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This article explores the pedagogical and psychological foundations of developing students’ competence in the educational process. It examines the role of effective teaching strategies, classroom practices, and learning environments in fostering students’ cognitive, communicative, and self-regulatory skills. The psychological characteristics discussed include motivation, self-esteem, emotional resilience, and individual learning differences. The study also highlights the importance of a student-centered approach, where teachers act as facilitators of personal growth and academic success. The findings emphasize that the integration of pedagogical and psychological principles is essential for nurturing competent, independent, and lifelong learners.